2016
DOI: 10.15207/jkcs.2016.7.3.149
|View full text |Cite
|
Sign up to set email alerts
|

Convergence Effective Factors for Work Performance among Returning to Workers with Industrial Accident

Abstract: For workers, industrial accidents exert a bad effect on the productivity, quality of life, and depress the morale. This study aimed to examine the overall influence on job performance of employees who returned to work after industrial accidents. This was a cross-sectional study using the data of 2013 and 2014 Panel Study of Worker's Compensation Insurance (PSWCI), and we performed logistic-regression analysis to analyze an affinity between general characteristics and job performance as independent variable and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Married men showed higher general life satisfaction and men who were divorced, separated, or widowed showed lower general life satisfaction compared to never married men. Married men have more opportunity to receive family support related to their disabilities and psychosocial stress, which may help male workers improve their health and employment outcomes compared to never married men and men who are divorced, separated, or widowed [39,40,41,42]. Also, married men may be more financially stable than men who are divorced, separated, or widowed because 49.3% of all Korean households were dual-earner households in 2017 [43], and this may lead to better general life satisfaction among married men.…”
Section: Discussionmentioning
confidence: 99%
“…Married men showed higher general life satisfaction and men who were divorced, separated, or widowed showed lower general life satisfaction compared to never married men. Married men have more opportunity to receive family support related to their disabilities and psychosocial stress, which may help male workers improve their health and employment outcomes compared to never married men and men who are divorced, separated, or widowed [39,40,41,42]. Also, married men may be more financially stable than men who are divorced, separated, or widowed because 49.3% of all Korean households were dual-earner households in 2017 [43], and this may lead to better general life satisfaction among married men.…”
Section: Discussionmentioning
confidence: 99%
“…여야 하는데 [4] 이에 부정적인 영향을 주는 요인으로 약물에 대한 지 식 부족 [12], 약물 복용에 대한 낮은 자기효능감 [13], 의료인과의 부 족한 의사소통 [14] 등이 확인되었다. 약물에 대한 지식 부족은 약물 이행을 저해하는 주요 요인으로, 노인의 신체 및 인지적 변화와 특성 을 고려하여 대상자가 이해하기 쉬운 교육을 진행해야 한다 [8].…”
Section: 성공적인 혈압관리를 위해서는 노인의 약물치료 이행도를 증진하unclassified
“…Workers injured by industrial accidents express psychological difficulties, aftereffects, and physical difficulties in performing their jobs [16]. As a result, workers injured by industrial accidents may have lower performance compared to their previous work performance and experience difficulties in returning to work and maintaining their work.…”
Section: Job Performance and Return To Workmentioning
confidence: 99%
“…Lee & Kim, 2018 [23] reported that personal factors (e.g., educational level, workplace, disability grade, and the presence of disability), environmental factors (e.g., economic activities, employment status, employment period, socioeconomic status, the length of recuperation, and work performance), and participation factors (e.g., the degree of others' help and difficulties in IADL) significantly affected job performance. This study selected explanatory variables by referring to the results of these previous studies [16,23].…”
Section: Factors For Predicting Work Performancementioning
confidence: 99%
See 1 more Smart Citation